2020
DOI: 10.1128/jvi.00090-20
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus 58 E7 T20I/G63S Variant Isolated from an East Asian Population Possesses High Oncogenicity

Abstract: Human papillomavirus (HPV) type 58 is the third most commonly detected HPV type in cervical cancer among Eastern Asians. Our previous international epidemiological studies revealed that HPV58 carrying an E7 natural variant, T20I/G63S (designated V1), was associated with a higher risk of cervical cancer. We recently showed that V1 possesses a greater ability to immortalize and transform primary cells, as well as degrading pRB more effectively, than the prototype and other common variants. In this study, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…Increased ERK phosphorylation was found in neural progenitor cells [ 50 ] and the rat fibroblast cell line 3Y1 [ 51 ], and human keratinocytes expressing HPV oncogene E7 or inhibitors of ERK signaling can reduce oncogene expression and inhibit a neoplastic phenotype through EGFR/MEK/ERK signaling [ 52 ] or K-Ras/ERK signaling [ 53 , 54 ]. In a skin carcinogenesis mouse model, papilloma formation was found in mice lacking DUSP5 and its regulation of nuclear ERK activity also served DUSP5 as tumor suppressor in epidermis Ras modulation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased ERK phosphorylation was found in neural progenitor cells [ 50 ] and the rat fibroblast cell line 3Y1 [ 51 ], and human keratinocytes expressing HPV oncogene E7 or inhibitors of ERK signaling can reduce oncogene expression and inhibit a neoplastic phenotype through EGFR/MEK/ERK signaling [ 52 ] or K-Ras/ERK signaling [ 53 , 54 ]. In a skin carcinogenesis mouse model, papilloma formation was found in mice lacking DUSP5 and its regulation of nuclear ERK activity also served DUSP5 as tumor suppressor in epidermis Ras modulation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these mutations were also found to be unique to lineage C (Supplementary Table S5). For HPV58, both epidemiological and experimental evidence indicated that linked mutations of C632T (E7:T20I) and G760A (E7:G63S), mostly found in sublineage A3, were positively associated with high oncogenicity [22,33,42]. While C632T uniquely occurred in 100% (n=19) of the Changsha sublineage A3 strains, G760A was found in all strains of sublineage A3 (n=19) and B1 (n=4) (Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…We then decided to provide further experimental evidence to explain their relative contribution to cancer risk. Indeed, when comparing these HPV58 E7 variants, V1 showed a greater ability to induce the immortalization and transformation of primary cells [ 259 ], promoting cell proliferation, migration, invasion, and increased tumour burden in athymic nude mice [ 260 ]. We also provided a molecular explanation for this.…”
Section: Genetic Variations Within E6 and E7 Oncoproteins Contribute To Their Differential Carcinogenicitymentioning
confidence: 99%
“…We also provided a molecular explanation for this. V1 can degrade pRb, as well as activate AKT and K-Ras/extracellular signal-regulated kinase (ERK) signalling pathways, more effectively than its prototype and other variants [ 259 , 260 ]. This can potentially explain the high prevalence of HPV58 in cervical lesions and its increased association with cervical cancer risks.…”
Section: Genetic Variations Within E6 and E7 Oncoproteins Contribute To Their Differential Carcinogenicitymentioning
confidence: 99%